Does Azospirillum brasilense and biostimulant improve the initial growth of rice sown at greater depths? - Oliveira, Carlos Eduardo da Silva [UNESP]; Zoz, Tiago; Vendruscolo, Eduardo Pradi; Andrade, Agner de Freitas; Seron, Cássio de Castro; Witt, Travis Wilson (Springer Nature, 2020)
The sowing operation is crucial for the proper initial establishment of seedlings and their development. However, there is a lack of studies about the effects of sowing depth of rice, as well as technologies that aid to mitigate the prejudicial effects caused by depth. In this way, the present work aimed to evaluate the initial growth of rice plants inoculated with Azospirillum brasiliense and treated with biostimulant sowed at different depths. Randomized complete block design with four replications was used, in a 4 × 4 factorial scheme. The first factor was composed of different seed treatments (a, control—without treatment; b, inoculation with A. brasilense; c, seed treatment with Stimulate® and d, inoculation with A. brasilense associated with seed treatment with Stimulate®). The second factor was composed of four sowing depths (1.0, 3.0, 5.0 and 7.0 cm). Treatment of rice seeds with A. brasilense and Stimulate® decreases the rate of emergence. The sowing at 7 cm depth decreases in 41.44% of the emergence, when compared to sowing at 1 cm. Inoculation with A. brasilense and sowing at increasing depths are prejudicial to the growth of rice crop.
Keywords: Biological fixation; Diazotrophic bacteria; Emergence; Oryza sativa; Tiller